2007
DOI: 10.1002/j.1545-7249.2007.tb00099.x
|View full text |Cite
|
Sign up to set email alerts
|

English Language Teachers Reflecting on Reflections: A Malaysian Experience

Abstract: Key characteristics of an efficient and effective English language teacher are fundamental pedagogical knowledge and understanding, awareness of meaningful classroom practices, linguistic capabilities, and positive attitudes and skills. Nurturing these traits among preservice teachers is difficult, especially when preservice teachers are working in a nonnative English language learning and teaching environment and when they have insufficient pedagogical and linguistic knowledge. One way of overcoming these dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…In this sense, our findings are in line with the studies that have reported that reflection-on-action develops teachers´ awareness (Schussler, Stooksberry & Bercaw, 2010), that it triggers transformations of teachers´ beliefs and points of view, as well as teacher´s instruction (Dixon & Wilke, 2007;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Manrique, 2013;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). Our findings also show the power of video analysis, that can enable teachers a unique opportunity to review and reflect on their positioning and it can foster changes in practices (Bower, Cavanagh, Moloney & Dao, 2011;Charteris & Smardon, 2013;Danielowich, 2014;Henessya & Deaneya, 2009;Kersting, Givvin, Sotelo & Stigler, 2010;Santagata & Angelici, 2010).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this sense, our findings are in line with the studies that have reported that reflection-on-action develops teachers´ awareness (Schussler, Stooksberry & Bercaw, 2010), that it triggers transformations of teachers´ beliefs and points of view, as well as teacher´s instruction (Dixon & Wilke, 2007;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Manrique, 2013;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). Our findings also show the power of video analysis, that can enable teachers a unique opportunity to review and reflect on their positioning and it can foster changes in practices (Bower, Cavanagh, Moloney & Dao, 2011;Charteris & Smardon, 2013;Danielowich, 2014;Henessya & Deaneya, 2009;Kersting, Givvin, Sotelo & Stigler, 2010;Santagata & Angelici, 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have reported that the process of reflection-on-action can play a vital role in fostering transformations of teachers´ beliefs, points of view, knowledge and strategies (Dixon & Wilke, 2007;Eilam & Poyas, 2009;Freedman, Bullock & Duque, 2005;Kabilan, 2007;Kang, 2007;Kucan, 2007;Manrique & Borzone, 2012;Pareja Roblin & Margalef, 2013;Schussler, 2006;Schussler, Stooksberry & Bercaw, 2010). For instance, Schussler, Stooksberry and Bercaw´s analysis of teachers´ dispositions in 35 teaching journals in U.S.A shows that those teachers who possessed the greatest awareness of their dispositions also showed a propensity to unpack their assumptions, adopting multiple perspectives, questioning the how and why of their thinking and actions and balancing the focus on students and the focus on the self.…”
Section: Teacher Education and Teacher Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflective practice also promotes self-improvement process that develops student teachers teaching quality (Ibrahim et al, 2008;Yaacob et al, 2014). It is also a key exercise that enables exploration of emerging thoughts, deeply held beliefs, changes in beliefs and perceptions, self-awareness of beliefs and principles and show converging patterns and trends (Albakri et al, 2012;Borg, 2008;Collier, 1999;Ismail et al, 2014;Kabilan, 2007;Woods, 1996).…”
Section: Criticalmentioning
confidence: 99%
“…Kabilan (2007) recognizes Malaysian students in remote and rural areas are not provided with the same level of instruction, especially in English language exposure, as students in urban areas which likely hinders the intent of the reform efforts. Kabilan (2007) goes on to recognize, "the emphases on English as an academic subject and a tool for economic attainment" (p. 681). So while curriculum reform can be seen as a tool for economic development, not all students are allowed to access this capital that is identified as central to participation in the economic imperatives.…”
Section: The Asian Experiencementioning
confidence: 99%